Waist-to-height ratio is a simple and practical alternative to waist circumference to diagnose metabolic syndrome in type 2 diabetes - Ma, Yi-Lin; Jin, Chun-Hua; Zhao, Cui-Chun; Ke, Jiang-Feng; Wang, Jun-Wei; Wang, Yu-Jie; Lu, Jun-Xi; Huang, Gao-Zhong; Li, Lian-Xi (Frontiers in Nutrition, 2022)
Background: As an indicator of abdominal obesity, waist circumference (WC) varied with race and gender in diagnosing metabolic syndrome (MetS).Therefore, it is clinically important to find an alternative indicator of abdominal obesity independent of these factors to diagnose MetS. Our aims were to evaluate the association between waist-to-height ratio (WHtR) and MetS and further determine whether WHtR could be used as a simple and practical alternative to WC to diagnose MetS in patients with type 2 diabetes mellitus (T2DM).Methods: This cross-sectional study recruited 8488 hospitalized T2DM patients including 3719 women aged from 18 to 94 years and 4769 men aged from 18 to 91 years. A WHtR cut-off of 0.52 was used to diagnose MetS in both men and women T2DM patients based on our previous study. The association of WHtR with MetS in T2DM patients was analyzed by binary logistic regression. The consistency of two diagnostic criteria for MetS according to WC and WHtR was determined by Kappa test.Results: The prevalence of MetS according to WHtR was 79.4% in women and 68.6% in men T2DM patients, which was very close to the prevalence of MetS according to WC in both women (82.6%) and men (68.3%). The prevalence of MetS diagnosed by WC in both men and women with WHtR ≥ 0.52 was significantly higher than in those with WHtR < 0.52 after adjustment for age and duration of diabetes (89.2.% vs. 38.7% for men; 92.8% vs. 57.4% for women; respectively, all p<0.001). Binary logistic regression analysis displayed that after adjusting for confounding factors, WHtR was significantly associated with the presence of MetS in both men and women (men: OR=4.821, 95%CI: 3.949-5.885; women: OR=3.096, 95%CI: 2.484-3.860; respectively, all p<0.001). Kappa test revealed that there was an excellent consistency between the diagnosis of MetS based on WC and on WHtR in T2DM patients (men: kappa value=0.929, 95%CI: 0.918-0.940; women: kappa value=0.874, 95%CI: 0.854-0.894; total: kappa value=0.911, 95%CI: 0.901-0.921; respectively, all p<0.001).Conclusions: WHtR is independently associated with the presence of MetS and can be used as a simple and practical alternative to WC to diagnose MetS regardless of gender in T2DM patients.